The differentiated instruction book of lists - Fox, Jenifer; Hoffman, Whitney, 1966- (San Francisco, CA. : Jossey-Bass, 2011)
'Hundreds of useful ideas for meeting the needs of each childThe Differentiated Instruction Book of Lists is the definitive reference for DI for teachers in grades K-12. Ready for immediate use, it offers over 150 up-to-date lists for developing instructional materials, lesson planning, and assessment. Organized into 12 convenient sections, the book is full of practical examples, teaching ideas, and activities that can be used or adapted to meet students' diverse needs. Coverage includes curriculum design, lesson planning, instructional strategies, assessment, classroom management, strategies by subject area (from Language Arts to Math to Physical Education), new media, etc. Offers an easy-to-use guide that gives quick tips and methods to plan effectively for delivering truly differentiated lessons Filled with helpful DI lists, lesson plans, strategies, assessments, and more Jennifer Fox is the author of the bestselling book Your Child's Strengths The Differentiated Instruction Book of Lists is a hands-on guide for meeting the instructional needs of all students so that they can reach their full potential'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Individualized instruction -- United States; Inclusive education -- United States; Mainstreaming in education -- United States; Classroom management -- United States